2015
DOI: 10.1039/c4ra17093h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of structural stability of cold adapted Candida antarctica lipase B (CaLB): in relation to pH, chemical and thermal denaturation

Abstract: The effect of pH on the conformational behavior of Candida antartica lipase B (CaLB) has been monitored by spectroscopic and calorimetric studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(57 citation statements)
references
References 51 publications
7
50
0
Order By: Relevance
“…The immobilization values were 35 and 33 mg/g for SBA-15-NH 2 G-PC and SBA-15-NH 2 G-CalB, respectively, similar to those obtained by Bautista et al [4] (36.1 mg/g) and slightly lower than that obtained by Serra et al [30] (44 mg/g), both using CalB as enzyme. The slightly higher incorporation of enzyme in the case of PC may be due to the fact that its size is somewhat smaller (3 × 3.2 × 6.6 nm) [31] and can enter into the pores more easily than CalB (3 × 4 × 6 nm) [32].…”
Section: Characterization Of the Synthesized Enzymatic Catalystmentioning
confidence: 99%
“…The immobilization values were 35 and 33 mg/g for SBA-15-NH 2 G-PC and SBA-15-NH 2 G-CalB, respectively, similar to those obtained by Bautista et al [4] (36.1 mg/g) and slightly lower than that obtained by Serra et al [30] (44 mg/g), both using CalB as enzyme. The slightly higher incorporation of enzyme in the case of PC may be due to the fact that its size is somewhat smaller (3 × 3.2 × 6.6 nm) [31] and can enter into the pores more easily than CalB (3 × 4 × 6 nm) [32].…”
Section: Characterization Of the Synthesized Enzymatic Catalystmentioning
confidence: 99%
“…This observation indicated that the unfolding of RCL was initiated at about 500 MPa and that the salt did not shift the beginning point of unfolding. In addition, the fluorescence intensity at 600 MPa was more than two times of that at atmospheric pressure, indicating that more hydrophobic area exposed to the solvent due to HHP treatment . This result indicated that the presence of KCl cannot prevent and alleviate the high pressure‐induced damage to the interior hydrophobic core of the lipase.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the fluorescence intensity at 600 MPa was more than two times of that at atmospheric pressure, indicating that more hydrophobic area exposed to the solvent due to HHP treatment. 29,39 This result indicated that the presence of KCl cannot prevent and alleviate the high pressure-induced damage to the interior hydrophobic core of the lipase. It could explain that the addition of KCl cannot improve the RCL unfolding stability at 600 MPa.…”
Section: Denaturation Of Rcl Measured By Ans Fluorescencementioning
confidence: 97%
“…The MG forms of proteins have remarkable secondary structure and few tertiary contacts related to the native state, but its compactness is somehow less than the native state [35][36][37][38]. However, there is some report that MG has more toxicity effects, but its mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 96%